1972
DOI: 10.1001/archinte.1972.03650050043007
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Secretion and Gastric Mucosal Morphology in Chronic Alcoholics

Abstract: Four to eight weeks after the cessation of alcohol intake, 70 alcoholics underwent gastric biopsies, gastric analysis, pancreozyminsecretin test, and liver biopsy. Biopsies revealed gastritis in 50% of body specimens and in 84% from the antrum. Correlation of biopsies with acid secretion revealed that maximal acid output (MAO) was 4.63 mEq/hr in atrophic gastritis, 22.40 mEq/hr in superficial gastritis and 26.97 mEq/hr in those with normal mucosa. There was no correlation between MAO and liver biopsy findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…the mucosal injury found in the majority of alcoholics [6][7][8]. In some studies an increased incidence of chronic gastritis in alcoholics has been dem onstrated [6,9] whereas other studies [8,10] did not reveal any evidence of alcohol play ing a role in the etiology of chronic gastritis. Furthermore, no association between alcohol consumption and the prevalence of peptic ulceration has been found [11,12].…”
mentioning
confidence: 99%
“…the mucosal injury found in the majority of alcoholics [6][7][8]. In some studies an increased incidence of chronic gastritis in alcoholics has been dem onstrated [6,9] whereas other studies [8,10] did not reveal any evidence of alcohol play ing a role in the etiology of chronic gastritis. Furthermore, no association between alcohol consumption and the prevalence of peptic ulceration has been found [11,12].…”
mentioning
confidence: 99%
“…3~ An improvement in histological gastritis was noted in 12 alcoholics following up to 9 months of abstinence from alcohol. 31 On the other hand, Brown et al 32 reported that chronic gastritis in patients with alcoholic cirrhosis was not higher than in controls. There is no doubt that alcohol abuse causes acute damage to the gastric mucosa, including hemorrhagic erosions after the ingestion of concentrated alcohol, although these lesions heal rapidly.…”
Section: Chronic Alcohol Abuse In Humansmentioning
confidence: 96%
“…The observations of D ionoso el al. [16] indi cated clearly that chronic ethanol ingestion is associated with an increas ed incidence of superficial and atrophic gastritis, and that the MAO in chronic alcoholics depends on the mucosal histology of the body of the stomach. 2…”
Section: Chronic Gastritis In Manmentioning
confidence: 98%
“…In spite of the observations made by these investigators [8,28,34], it is still difficult to assess the role of ethanol in the development of atrophic gastritis in chronic alcoholics, since many of these alcoholics were undernourished or malnourished when the observations were made. Recently, Dinoso et al [16] investigated 70 male chronic alcoholics who were admitted to a rehabilitation center for treat ment of alcoholism. Gastric acid secretory study and histological study of the gastric mucosa were performed.…”
Section: Chronic Gastritis In Manmentioning
confidence: 99%
See 1 more Smart Citation